1995
DOI: 10.1016/0378-1097(95)00145-u
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic suppression of a mutation: Characterization of an autoinducer-independent LuxR

Abstract: The Vibrio fischeri luminescence genes are activated by the LuxR protein and a diffusible signal termed the autoinducer. LuxR consists of two domains, a C-terminal transcriptional activator domain, and an N-terminal autoinducer-binding domain, which serves to regulate the function of the C-terminal domain. We have isolated and characterized an intragenic suppressor of a mutation that maps to the N-terminal domain and blocks autoinducer binding. The suppressor changes an alanine residue at position-221 in the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Those in the N-terminal domain are defective in signal binding and thus transcriptional activation. Those with substitutions in the C-terminal domain are capable of signal binding but are nevertheless defective in transcriptional activation (21,31). We sought to determine whether signal binding mutant LuxR proteins were capable of repressing p35LB10 lacZ transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Those in the N-terminal domain are defective in signal binding and thus transcriptional activation. Those with substitutions in the C-terminal domain are capable of signal binding but are nevertheless defective in transcriptional activation (21,31). We sought to determine whether signal binding mutant LuxR proteins were capable of repressing p35LB10 lacZ transcription.…”
Section: Resultsmentioning
confidence: 99%
“…The amino-terminal regions of the LuxR-like proteins are involved in HSL binding, and the C-terminal domains of the proteins are responsible for oligomerization and promoter DNA binding. A similar promoter element is bound by each of the LuxR-type proteins (Slock et al 1990;Choi andGreenberg 1991, 1992;Stevens et al 1994;Poellinger et al 1995;Stevens and Greenberg 1997;Stevens et al 1999).…”
Section: Gram-negative Bacteria Use Homoserine Lactones As Wordsmentioning
confidence: 99%
“…Previous studies with recombinant Escherichia coli have identified amino acid point mutations in the C-terminal domain of LuxR that can be placed into two categories: (i) those that affect the ability of LuxR to activate transcription of the lux operon (residues 184,193,195,197,217, and 230) (17,19) and (ii) those that result in a form of LuxR that is capable of autoinducer-independent activation of transcription of the lux operon (residues 164, 221, 223, and 246) (14,18). Deletion mutagenesis analysis of the C-terminal domain of LuxR was also used to identify regions of LuxR critical for its ability to activate transcription of the lux operon (3,4).…”
mentioning
confidence: 99%
“…However, since random mutagenesis of the C-terminal domain of LuxR has previously identified single amino acid substitutions that allow LuxR to activate transcription of the lux operon independent of autoinducer (14,18), all 38 of the alanine-substitution mutants were also tested for this autoinducer-independent phenotype in the luminescence assay. Strains were grown as described above, except in the absence of autoinducer and at 31°C, since the mutation in luxI encoded on pJR551 is a temperaturesensitive mutation that will allow LuxI to synthesize autoinducer below 30°C (14). None of the alanine-substitution mutants was shown to exhibit an autoinducer-independent phenotype (data not shown).…”
mentioning
confidence: 99%